Surgical Management of Biliary Duct Hamartoma in a Cat: A Case Report - Manap, Nur Ainina Ab; Chong, Tey Yu; Arip, Erni Wati Mohd; Radzi, Rozanaliza; Zakaria, Muhamad Alif; Tahir, Nur Diyana Mohamad; Zahli, Nurul Izzati Uda (Universitas Airlangga, 2025)
Cysts in the liver or biliary duct are uncommon in veterinary medicine. A multiloculated, fluid-filled liver cyst measuring 18 cm in diameter was detected in a two-year-old spayed female mixed-breed cat via radiography and computed tomography. The cyst was attached to the medial lobe aspect of the liver and continued with the gall bladder. Cystectomy and omentopexy were performed, and the resected cyst was examined histologically. Histologic analysis revealed variable-sized cystic spaces lined by low simple cuboidal and attenuated epithelium. The cyst wall was composed of thick collagenous stroma containing entrapped islands of the hepatic parenchyma, which included atrophied hepatocytes, dilated sinusoidal spaces filled with erythrocytes, and randomly distributed hyperplastic bile ducts. These histologic findings were consistent with biliary duct hamartoma. The cat had an uneventful recovery, and no recurrence was observed one-year post-surgery.